Uji Efektivitas Rizobakteri dalam Pengendalian Penyakit Antraknosa pada Buah Cabai Merah (Capsicum annum L.) Secara In Vivo - Eka Widianingsih; Sulastri Isminingsih; Endang Sulistyorini; Andree Saylendra (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Chili (Capsicum annuum L.) is the most commercially cultivated horticultural crop compared to other vegetables. The decline in chili production in Indonesia can occur due to several factors, including attacks of anthracnose caused by the fungus Colletotricum sp. Control can be done by using biological agents that are environmentally friendly and able to induce plant resistance to disease systemically. The objective of this study was to determine the effectiveness of rhizobacteria in controlling anthracnose disease on red chili fruit (Capsicum annum L.) in vivo. This research was conducted in the Laboratory of Soil and Agroclimate and Basic Science and Plant Protection, Faculty of Agriculture, Sultan Ageng Tirtayasa University, Serang City, Banten, on September to November 2024. This study used a one-factor Completely Randomised Design (RAL) with four replications. The treatments consisted of seven levels, namely (E0-) without rhizobacteria on infected chillies, (E0+) the use of fungicides on infected chillies, and five selected rhizobacterial isolates derived from oil palm plant soil. The results showed that rhizobacterial isolates could control anthracnose disease caused by the fungus Colletotrichum sp. on red chilli fruit in vivo with different effectiveness. The treatment of rhizobacterial isolate E5 was the best in reducing the incubation period of the fungus Colletotrichum sp. by 5 days, the percentage of anthracnose disease incidence by 66.67% with moderate disease resistance, and the percentage of anthracnose disease intensity by 28.32% at the end of observation and the average rate of chilli fruit weight loss by 17.31%, although higher than the positive control treatment (E0+).